The Digital Identity of Women on Social Networking Sites: A Critical Analytical Perspective - Lamia Djoudi (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Social media platforms have enabled women to positively assert their presence, transcending the traditional media's marketed corporeal representations. It is imperative that women strategically cultivate and manage their digital identities within the virtual landscape to leverage self-marketing and reputation building. This is particularly crucial given their substantial representation across various social media platforms within the societal context.